Alleviative effects of foraging exercise on depressive-like behaviors in chronic mild stress-induced ischemic rat model. (2nd January 2022) - Tao, Xi; Wu, Siyuan; Tang, Wenjing; Li, Lu; Huang, Lijun; Mo, Danheng; Liu, Chujuan; Song, Tao; Wang, Shuling; Wang, Jia; He, Juan
ABSTRACT: Background: Poststroke depression (PSD) is a common complication that seriously affects the functional recovery and prognosis of an individual. As some patients with PSD fail to respond to drug therapy, it is urgent to find a viable alternative treatment. Methods: An active exercise program known as foraging exercise (FE), using food as bait, was designed. First, focal ischemia and chronic unpredictable mild stress (CUMS) were used to establish a PSD model in rats. FE was then performed for 4 weeks. Body weight and behavioral assessments were conducted at the end of the 4 th and 8 th weeks. Results: After 8 weeks, the results revealed that, compared with the PSD group, the behavioral scores of the rats in the PSD/FE group were significantly improved, the expression of Iba-1 in the affected frontal lobe and striatum was decreased, and serum levels of IL-6 and the IL-6/IL-10 ratio were downregulated. However, the ratio of residual brain volume in rats that had experienced CUMS was significantly less than that in the stroke group. Conclusion: FE can alleviate the behavioral scores of PSD rats, and its mechanism may be related to a modulation of the immune-inflammation response of microglia. Furthermore, chronic, persistent stress may increase the volume of cerebral infarction after stroke.